2017
DOI: 10.3390/bs7040067
|View full text |Cite
|
Sign up to set email alerts
|

Health Philosophy of Dietitians and Its Implications for Life Satisfaction: An Exploratory Study

Abstract: Studies of health providers suggest that satisfaction with life is related to their values and sense of purpose which is best achieved when their professional role is in harmony with personal philosophy. Cross-sectional surveys suggest that personal health beliefs and practices of health professionals influence their clinical counseling practices. However, little is known about the influence of health philosophy on the personal satisfaction with life for dietitians. This study recruited a randomly selected, cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
3
1
Order By: Relevance
“…The response to our survey was slightly lower than anticipated. However, our response rate of 36% was higher than other national surveys of dietitians (30, 6062, 71). Our survey was initially sent in the summertime, which may have been a time where program directors were away from campus, on vacation, or contending with other program issues such as accreditation site visits.…”
Section: Discussioncontrasting
confidence: 69%
“…The response to our survey was slightly lower than anticipated. However, our response rate of 36% was higher than other national surveys of dietitians (30, 6062, 71). Our survey was initially sent in the summertime, which may have been a time where program directors were away from campus, on vacation, or contending with other program issues such as accreditation site visits.…”
Section: Discussioncontrasting
confidence: 69%
“…The factor structure of the set of observed variables with confirmatory factor analysis tested the hypothesis that a relationship between these observed variables and their underlying latent constructs exist. The resulting path coefficients demonstrated that there was a small effect for lifestyle on life satisfaction for women (r=0.27, p<0.000) and a moderate effect for our small sample of men (r=0.694, p<0.000) as we described in a previous paper [21]. Although there was shared variance between healthy lifestyle and wellness philosophy, it was small and not significant (r=0.028, p=0.521).…”
Section: Resultssupporting
confidence: 54%
“…Self-reported variables such licenses or certifications held and specific integrative therapies were included as measures of role identity and practice specialization. The health philosophy of registered dietitians was described in greater detail in our previous paper [21].…”
Section: Methodsmentioning
confidence: 99%
“…Not only the nutritionists' attributions [7] influence their job satisfaction, but also the knowledge acquired during undergraduate and postgraduate courses. Moreover, Grace-Farfaglia et al [17] found that life satisfaction of US nutritionists were influenced directly and positively by a greater orientation towards wellness and a healthy lifestyle. Thus, undergraduate courses should comprise modules on wellness and health self-management, which contribute to life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty years after the regulation of the nutritionist profession in Brazil -guaranteed by the enactment of Law No.5276/1967 and later by Law No.8234/1991 [14,15] -and development of several career opportunities in food service, there has been little evidence on the job satisfaction of these professionals in this area in the last years, both in Brazil [11] and in other countries [12,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%